IN SITU WATER QUALITY ASSESSMENT AND COLIFORM CLASSIFICATION IN BATANG LAYAR, SARAWAK - Sabella, Justin; Samuel, Lihan; Siti Zaharah, Zamri; Toh Seng, Chiew; Yus Amira, Yusaimi; Henry Adam, Segaya; Selvana Eyra, Felix; Gabriel Tonga, Noweg; Jongkar, Grinang; Kelvin, Egay (VOLKSON PRESS and Zibeline International, 2025)
The Batang Layar river in Sarawak, Malaysia, is a vital water resource for local communities, supporting aquaculture, agriculture, transportation, recreation, and drinking water supply. Despite its significance, the river’s water quality remains understudied, raising public health concerns due to potential contamination from anthropogenic activities. This research evaluates water quality of the river at four (4) sites (Nanga Tiga, Spak, Lubau, and New Layar Bridge) through in-situ physicochemical analysis and microbial profiling, focusing on coliform bacteria as pollution indicators. Results show that faecal coliform counts (FCC) and total coliform count (TCC) at these sites are classified under Class III of Malaysia’s National Water Quality Standard (NWQS), indicating significant contamination and requiring substantial treatment. Notably, The New Layar Bridge site showed highest contamination levels (FCC: 817 CFU/100 mL; TCC: 12,517 CFU/100 mL), suggesting anthropogenic impacts from domestic waste or urban runoff. Molecular techniques via (GTG)5 PCR fingerprinting and 16S rRNA sequencing identified ten bacterial genera, with Acinetobacter (28.57%), Chromobacterium (14.29%), and Escherichia (9.52%) being the most prevalent genera, commonly associated with faecal contamination. This study highlights the urgent need for effective sustainable management strategies, including proper waste disposal practices and regular monitoring, to preserve the rivers in the study area.